Single-incision laparoscopic ileocecal resection in a 10-year-old child with appendiceal neuroendocrine tumor - Ayana Goto; Nobuhisa Matsuhashi; Takao Takahashi; Yuta Sato; Shinya Hirata; Toshiyuki Tanahashi; Satoshi Matsui; Hisasi Imai; Yoshihiro Tanaka; Kazuya Yamaguchi; Kazuhiro Yoshida (World Journal of Surgical Oncology, 2019)
Abstract Background In Japan, the majority of gastrointestinal tract neuroendocrine tumors (NETs) have been reported to originate from the rectum, and appendiceal NETs are relatively rare. Preoperative diagnosis is very difficult and it is diagnosed after appendectomy. Pediatric appendiceal NET is a disease with a good prognosis. However, in rare cases, lymph node metastasis could occur and additional resection is required. Case presentation A 10-year-old boy complained of right lower quadrant abdominal pain and underwent an appendectomy under a diagnosis of acute appendicitis in previous hospital. The final diagnosis was appendiceal NET, so he was referred to our department for additional resection. The tumor was found in the base of the appendix and invasively reached the subserosal layer with obvious vascular invasion. His Ki-67 index was 1 to 2%, so we classified it as appendiceal NET G1 according to the WHO 2015 classification. We considered the possibility of a tumor remnant or lymph node metastasis, so we performed single-incision laparoscopy with D3 lymph node dissection. The pathological diagnosis revealed no tumor remnant but metastasis to one lymph node. He was discharged on the 9th postoperative day. There has been no recurrence at 3 years and 7 months after surgery. Conclusion When the tumor size is 10–20 mm, the frequency of lymph node metastasis in some reports is variable, and there is no consensus yet on the indications for additional resection. However, there are definitely a certain number of cases with lymph node metastasis that require additional resection. In the present patient, long-term survival can be obtained by additional resection. At present, factors such as the presence of vascular or lymph node invasion and the malignancy grade and tumor’s location must be considered on a case-by-case basis. Although the incidence rate of appendiceal NET is rare, the diagnosis can be made only during postoperative pathological examination; thus, reliable histopathological examination is required.